The State of Cardiovascular Disease in the Kyrgyz Republic - Ryskul B. Kydyralieva (University Library System, University of Pittsburgh, 2013)
Using the methods of estimation of economic efficiency we have made calculation of the economic losses connected to cardiovascular diseases. It was shown that the economic damage from premature death rate and physical inability from CVD in our country totaled more than 14 billions soms (near 360 millions $ USA) in 2007 (2). It dictates necessity of the urgent organization of struggle against cardiovascular diseases for stop the deterioration of health parameters of Kyrgyz population and prevention of serious social consequences with negative economic effect.